Uniformidade de distribuição longitudinal de fertilizantes de um mecanismo dosador com rosca helicoidal dupla - Cruz, Wagner Alexandre Silveira da (2021)
With the constant increases in the demand for food, an increase in crop productivity is increasingly necessary. For this to occur, the use of more efficient techniques and equipment is essential. This research aimed to evaluate the performance of the double helical thread fertilizer dosing mechanism, in the longitudinal distribution of fertilizer, when subjected to different levels of longitudinal and transversal inclination with different types of fertilizer. The research was carried out at the Agricultural Machinery Research and Development Laboratory (LASERG, in Portuguese) of the Federal University of Santa Maria. A bench was used for testing fertilizer dosing and a conveyor system was used to simulate the displacement of the seeder-fertilizer. Two dosing mechanisms were used: one with double helical thread and the other, as a matter of performance comparison, with transversal overflow discharge. The evaluated inclinations were as follows: 0º level, 11º ascending, 11º descending, 11º left and 11º right. Three fertilizers of different granulometry were used: granular mixture, grain mixture and mash. The experiment was arranged in a completely randomized design (CRD), in a three-factor arrangement (dosing mechanism, slope and type of fertilizer), and 40 repetitions of each treatment were carried out. The response variable analyzed was the amount of fertilizer dosed every 50 mm. It is possible to observe that the longitudinal distribution of fertilizers of the two mechanisms did not show a statistically significant difference, with coefficients of variation (CV) of 26.69% for the double helical feeder and 33.25% for the transversal overflow feeder. According to the CV, the feeder with double helical thread showed a better performance to reduce the effects of longitudinal and transverse inclinations. The two feeders showed the best performance in the dosing of mash-type fertilizer. In general, the two feeders showed unsatisfactory performance in the uniformity of fertilizer dosing on the line.